A function of spalt major as a sequence-specific DNA binding transcription factor mediates repression of knirps in the Drosophila wing imaginal disc. - Ostalé, C.M.; Prado, A.D.; Martín, M.; Esteban, N.; López-Varea, A.; de Celis, J.F. (Developmental Biology, 2024)
The Spalt transcriptional regulators participate in a variety of cell fate decisions during multicellular development. Vertebrate Spalt proteins have been mostly associated to the organization of heterochromatic regions, but they also contribute regulatory functions through binding to A/T rich motives present in their target genes. The developmental processes in which the Drosophila spalt genes participate are well known through genetic analysis, but the mechanism by which the Spalt proteins regulate transcription are still unknown. Furthermore, despite the prominent changes in gene expression associated to mutations in the spalt genes, the specific DNA sequences they bind are unknow. Here, we analyze a DNA fragment present in the regulatory region of the knirps gene. Spalt proteins are candidate repressors of knirps expression during the formation of the venation pattern in the wing disc, and we identified a minimal conserved 30bp sequence that binds to Spalt major both in vivo and in vitro. This sequence mediates transcriptional repression in the central region of the wing blade, constituting the first confirmed case of a direct regulatory interaction between Spalt major and its target DNA in Drosophila. Interestingly, we also find similar sequences in a set of eight novel candidate Spalt target genes, pointing to a common mechanism of transcriptional repression mediated by Spalt proteins.